ASUHAN KEBIDANAN BERKELANJUTAN PADA NY. N, NY.H, NY.S DI PMB YALIMAH, S.Tr.,Keb - Ima, Yalimah (Universitas Aisyah Pringsewu, 2024)
Continuity of Care (COC) is a service that is achieved when a continuous relationship is established between the client and the midwife. Sustainable care is related to the quality of service from time to time which requires continuous contact between clients and professional health workers, of course with midwives who have APN (Normal Childbirth Care) certificates, to achieve the SDG target by 2030, namely reducing MMR. below 70 per 100,000 live births and by 2030 end preventable deaths of infants and toddlers. Therefore, the role of midwives as health workers is to carry out continuity of care and have standardized APNs able to reduce MMR and IMR (Noorbaya et al., 2019). The method used in comprehensive care for pregnant, maternity, postpartum, BBL and family planning women is a type of descriptive research using a case study approach. A case study is research carried out by examining a problem through a case consisting of a single unit. The case study was carried out at PMB Yalimah for 4 weeks, the results of the care showed that continuous care from pregnancy to birth control had been carried out in accordance with the standards of care, complementary care in the form of ginger compresses was effective in alleviating back pain in pregnant women, binahong leaves were effective in speeding up the healing process of perineal wounds